The Effect of Celebrity Testimonials on Generation Z Consumer Purchase Intention in Padang City - Asria, Maya; Vera, Nevia Prima (Pascasarjana STIE Amkop Makassar, 2025)
The development of social media has changed consumer behaviour patterns, especially in generation Z who are very active in the digital environment. One of the marketing strategies that is widely used today is the use of celebrity testimonials as a form of promotion to build trust and attract consumer buying interest. This study aims to examine the influence of celebrity testimonials on the purchase intention of generation Z consumers. The research was conducted using a quantitative approach and a survey design using a questionnaire. The population in this study were generation Z consumers in Padang City who actively use social media and follow certain celebrities or influencers. Data were analysed using simple linear regression. Theoretical studies in this study include marketing communication theory, source credibility theory, and consumer behaviour concepts. This article is the initial part of a broader research and will be continued with data-based quantitative analysis.